Применение тепловидения в энергосберегающих технологиях - Гришаева, А. Н. (ХНУРЕ, 2019)
The report indicates the thermal monitoring specificities of lateral boundary building constructions. We have presented the thermal imaging audit results of the KNURE hostel building and used equipment. The requirements for conduct-ing thermal imaging in natural conditions are presented as well. We have found a number of defects that lead to heat loss. A quantitative assessment of heat losses was made for one of the defects, namely, the wetted joint of the building. The method for estimating heat losses is given. We have also given the recom-mendations for eliminating heat leaks from the building. The ways to improve the accuracy of quantitative assessment of heat losses are indicated.